Simplifying Radicals

Algebra Level 1

Simplify x 3 9 \sqrt[9]{x^3} .

x 27 \sqrt[27]{x} x 6 \sqrt[6]{x} x 3 \sqrt[3]{x}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Marvin Kalngan
Aug 7, 2020

x 3 9 = ( x 3 ) 1 9 = x 3 9 = x 1 3 = x 3 \sqrt[9]{x^3}=\left (x^3\right)^{\frac{1}{9}}=x^{\frac{3}{9}}=x^{\frac{1}{3}}=\boxed{\sqrt[3] {x}}

x 3 9 = x 3 3 3 = x 3 \color{#3D99F6} \sqrt[9] {x^3}\color{#BA33D6}=\color{#D61F06}\sqrt[3] {\sqrt[3] {x^3}}\color{cyan}=\color{#20A900} \sqrt[3] x .

Mahdi Raza
Aug 21, 2020

x 3 9 = x 3 9 = x 1 3 = x 3 \Large{\sqrt[9]{x^3} = x^{\frac{3}{9}} = x^{\frac{1}{3}} = \sqrt[3]{x}}

Brilliant Mathematics Staff
Aug 1, 2020

Using the law of indices,

x 3 9 = ( x 3 ) 1 9 = x 3 1 9 = x 3 / 9 = x 1 / 3 = x 3 . \large \sqrt[9]{x^3} = (x^3)^{\frac19} = x^{3 \cdot \frac19} = x^{3/9} = x^{1/3} = \boxed{\sqrt[3]{x}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...